1996
DOI: 10.1083/jcb.134.6.1519
|View full text |Cite
|
Sign up to set email alerts
|

Association between a transmembrane protein tyrosine phosphatase and the cadherin-catenin complex.

Abstract: Abstract. Cadherins are calcium-dependent cell adhesion molecules that play fundamental roles in embryonic development, tissue morphogenesis, and cancer. A prerequisite for their function is association with the actin cytoskeleton via the catenins. Tyrosine phosphorylation of 13-catenin, which correlates with a reduction in cadherin-dependent cell adhesion, may provide cells with a mechanism to regulate cadherin activity. Here we report that ~3-catenin immune precipitates from PC12 cells contain tyrosine phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(164 citation statements)
references
References 57 publications
(88 reference statements)
6
158
0
Order By: Relevance
“…This is even more intriguing since a molecular cross-talk between Wnt and EGF signalling is well known (Dierick and Bejsovec, 1999). Besides the kinases, several protein tyrosine phosphatases have been linked to b-catenin function (Hoschuetzky et al, 1994;Brady-Kalnay et al, 1995;Kypta et al, 1996). Future work will reveal which of the kinases or phosphatases is crucial for maintaining b-catenin in a dephosphorylated state in the case of sFRP-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This is even more intriguing since a molecular cross-talk between Wnt and EGF signalling is well known (Dierick and Bejsovec, 1999). Besides the kinases, several protein tyrosine phosphatases have been linked to b-catenin function (Hoschuetzky et al, 1994;Brady-Kalnay et al, 1995;Kypta et al, 1996). Future work will reveal which of the kinases or phosphatases is crucial for maintaining b-catenin in a dephosphorylated state in the case of sFRP-mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The focal adhesion molecules β-catenin and p130cas are substrates for LAR (Kypta et al 1996). Dephosphorylation of p130cas by LAR reduces it stability and leads to p130cas degradation, an event that is associated with cell death (Weng et al 1999).…”
Section: Lar and R2a Subfamilymentioning
confidence: 99%
“…LAR-PTP (Kypta et al, 1996;Mü ller et al, 1999) has been shown to interact with and dephosphorylate ␤-catenin. Additionally, overexpression of LAR-PTP correlates with prevention of ␤-catenin phosphorylation and inhibition of epithelial cell migration (Mü ller et al, 1999).…”
Section: Destabilizing Adhesions: Altering the Balance Between Phosphmentioning
confidence: 99%